1998
DOI: 10.1002/(sici)1522-9505(19981101)260:1<5::aid-apmc5>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Graft copolymerization of vinyl monomers on cellulosic materials

Abstract: Graft copolymers of acrylonitrile, ethyl acrylate, methyl acrylate, ethyl methacrylate and methyl methacrylate and of acrylonitrile/ethyl methacrylate and acrylonitrile/methyl methacrylate monomer mixtures on carboxymethylcellulose (degree of substitution 0.4–0.5) were prepared by use of ceric ion initiator in aqueous medium. The extent of graft polymer formation was measured in terms of graft level, molecular weight of grafted polymer chains and frequency of grafting as function of ceric ion concentration. It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…Many of the graft copolymers obtained to date have better safety and biocompatibility properties than the natural molecule and have found applications in the development of selective permeable membranes and outstanding sorption agents and in the fabrication of drug delivery systems (Gupta et al 2002). A wide variety of vinyl monomers have been grafted onto cellulose using different initiation systems (Subasini et al 1981;Ighodalo and Theophilus 1993;Okieimen and Ogbeifun 1996;Canche-Escamilla et al 1997;Okieimen 1998;Saikia and Ali 1999;Gupta and Sahoo 2000;Gupta et al 2002;Pradeep et al 2004;Roma´n-Aguirre et al 2004;Anuradha and Malvika 2005;Bikkullova et al 2005;Elisabetta et al 2005;Ferdous 2005; Ghanshyam et al 2005;Mehmet and Temuz 2005;Okieimen et al 2005;Trivedi et al 2005).…”
Section: Introductionsupporting
confidence: 91%
“…Many of the graft copolymers obtained to date have better safety and biocompatibility properties than the natural molecule and have found applications in the development of selective permeable membranes and outstanding sorption agents and in the fabrication of drug delivery systems (Gupta et al 2002). A wide variety of vinyl monomers have been grafted onto cellulose using different initiation systems (Subasini et al 1981;Ighodalo and Theophilus 1993;Okieimen and Ogbeifun 1996;Canche-Escamilla et al 1997;Okieimen 1998;Saikia and Ali 1999;Gupta and Sahoo 2000;Gupta et al 2002;Pradeep et al 2004;Roma´n-Aguirre et al 2004;Anuradha and Malvika 2005;Bikkullova et al 2005;Elisabetta et al 2005;Ferdous 2005; Ghanshyam et al 2005;Mehmet and Temuz 2005;Okieimen et al 2005;Trivedi et al 2005).…”
Section: Introductionsupporting
confidence: 91%
“…If the resulting FT-IR spectrum does not identify the unique peak of the grafting vinyl monomer, the product is a counterfeit. A number of such yarns have been prepared by grafting different vinyl monomers onto cellulose [10][11][12][13] and starch [14,15]. The present study was undertaken with the aim of developing improved conditions for methacrylamide (MAam; see Figure 1) or 2-hydroxyethylmetacrylate (HEMA; see Figure 2) graft copolymerization onto flax yarn [13,16].…”
mentioning
confidence: 99%
“…The apparent low reactivity of the backbone polymer has been attributed to the two‐phase nature of the polymerization system and the state of aggregation of the backbone polymer,35, 36 considered the determinant of the availability of the anhydroglucose units for grafting. It has been suggested that efforts aimed at improving the frequency of grafting on cellulosic materials and the extent of modification of the backbone polymer must consider methods of enhancing the accessibility of the backbone polymer to reactant molecules and the number of reaction sites in the polymerization medium and of extending the duration of homogeneity during the reaction process 37…”
Section: Resultsmentioning
confidence: 99%